A novel nonlinear controller design of three-phase grid-tied photovoltaic system - Zaghar, Fatim-Zahra; Hekss, Zineb; Rafi, Mohamed; Echalih, Salwa; Ridah, Abdraouf (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This paper explores the challenges associated with the control of a two-stage three-phase electrical grid connected to a photovoltaic (PV) system. The core control objectives encompass: i) Maximizing the utilization of available power from the PV panel; ii) Regulating the DC-link voltage to a predetermined reference; and iii) Ensuring power factor correction (PFC) on the grid side. To achieve these objectives, two loops nonlinear controller are developed. In the outer loop, the duty cycle of a boost converter is controlled using integral backstepping technique with the perturb & observe (P&O) algorithm, which provides reference voltages to track maximum power points, and Lyapunov theory to ensure the system’s stability. In addition, the Inner loop is designed using proportional integrator (PI) controller to ensure the unit power factor correction. An assessment of the proposed method is conducted through a comparative study with the backstepping technique, demonstrating the effectiveness of the suggested solution. The results have been validated by numerical simulation within MATLAB/Simulink power systems environment.